Portable UV-C device to treat high flow of infectious aerosols generated during clinical respiratory care - Richard Vincent; David Rapoport; Priti Balchandani; Joseph Borrello; Michael Schotsaert; Robert Karlicek; Gabriel Laghlali; Prajakta Warang; Seokchan Park; Gagandeep Singh; Isabella Morgan; James Paredes; et al. (Scientific Reports)
Abstract Respiratory interventions including noninvasive ventilation, continuous positive airway pressure and high-flow nasal oxygen generated infectious aerosols may increase risk of airborne disease (SARS-CoV-2, influenza virus) transmission to healthcare workers. We developed and tested a prototype portable UV-C254 device to sterilize high flows of viral-contaminated air from a simulated patient source at airflow rates of up to 100 l/m. Our device consisted of a central quartz tube surrounded 6 high-output UV-C254 lamps, within a larger cylinder allowing recirculation past the UV-C254 lamps a second time before exiting the device. Testing was with nebulized A/PR/8/34 (H1N1) influenza virus. RNA extraction and qRT-PCR showed virus transited through the prototype. Turning on varying numbers of lamps controlled the dose of UVC. Viability experiments at low, medium and high (100 l/min) flows of contaminated gas were conducted with 6, 4, 2 and 1 lamp activated (single-pass and recirculation were tested). Our data show 5-log reduction in plaque forming units from a single lamp (single- pass and recirculated conditions) at high and low flows. UVC dose at 100 l/m was calculated at 11.6 mJ/cm2 single pass and 104 mJ/cm2 recirculated. The protype device shows high efficacy in killing nebulized influenza virus in a high flow of contaminated air.